2018
DOI: 10.1073/pnas.1810598115
|View full text |Cite
|
Sign up to set email alerts
|

DPYSL3 modulates mitosis, migration, and epithelial-to-mesenchymal transition in claudin-low breast cancer

Abstract: SignificanceMass spectrometry-based proteogenomics of patient-derived xenografts (PDXs) identified dihydropyrimidinase-like-3 (DPYSL3) as a multilevel (RNA/protein/phosphoprotein) expression outlier specific to a claudin-low (CLOW) PDX. DPYSL3 has established functions in neural cell migration and axon outgrowth but is understudied in breast cancer. Here, we demonstrate that loss of DPYSL3 promotes cell-cycle arrest, multinucleation, and collapse of the vimentin microfilament network associated with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…DPYSL3 is also reported to play a role in cell migration and metastasis suppression in liver and prostate cancer [31][32][33]. In contrast, DPYSL3 is positively associated with metastasis and a poor outcome in breast cancer, renal cell carcinoma, gastric and pancreatic cancer [34][35][36][37]. Our study indicates that DPYSL3 acts as a promoter of cancer progression supported by the loss of DPYSL3 reduced cancer migration and EMT.…”
Section: Discussionmentioning
confidence: 52%
“…DPYSL3 is also reported to play a role in cell migration and metastasis suppression in liver and prostate cancer [31][32][33]. In contrast, DPYSL3 is positively associated with metastasis and a poor outcome in breast cancer, renal cell carcinoma, gastric and pancreatic cancer [34][35][36][37]. Our study indicates that DPYSL3 acts as a promoter of cancer progression supported by the loss of DPYSL3 reduced cancer migration and EMT.…”
Section: Discussionmentioning
confidence: 52%
“…C ancer proteogenomics integrates data from cancer genomics and transcriptomics with cancer proteomics to provide deeper insights into cancer biology and therapeutic vulnerabilities. Both by improving the functional annotation of genomic aberrations and through insights into pathway activation, this multi-dimensional approach to the characterization of human tumors shows promise for application to precision oncology [1][2][3][4][5][6][7] Here we address tissue requirements for proteogenomics, which restricts translational research opportunities and applicability to cancer diagnostics. For example, the Clinical Proteomic Tumor Analysis Consortium (CPTAC) requires at least 100 mg of tumor tissue, which typically yields quantitative information on >10,000 proteins and >30,000 phosphosites per sample 8 .…”
mentioning
confidence: 99%
“…Among these, CLBC share features with mammary stem cells, enhances the expression of epithelial-mesenchymal transition (EMT) and stem cell marker molecules, while the expression of tight junction proteins Claudins and E-cadherin is decreased. 5,6 Clinical data and genetically engineered mouse models have shown that CLBC is more resistant to chemotherapeutic agents and has a worse prognosis than BLBC. 7,8 However, no specific targeted treatment exists for CLBC.…”
Section: Introductionmentioning
confidence: 99%